2008
DOI: 10.1038/cmi.2008.15
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effect of CD40 and TNF-Signaling on the Chemokine/Chemokine Receptor Expression and Function of the Human Monocyte-Derived Dendritic Cells

Abstract: A key and limiting step in the process of human monocyte-derived dendritic cells (mDCs) for clinical use is their in vitro maturation and in vivo migration. We previously observed that CD40 signal facilitated human mDC growth and maturation. To further explore this process, mDCs generated with GM-CSF and IL-4 were co-cultured with apoptotic tumor cells for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…In contrast, CD4+ T EM cells gain access to reactive LNs via CXCR3-independent means to interact with DCs and increase future T cell priming through CD40 upregulation [49]. Once T EM cells enter the LN, it is unknown if CD8+ or CD4+ interactions with DCs are also dependent on CXCR3 and its ligands, although it has been shown that CD40L stimulated DCs increase expression of CXCL10 [77]. Future studies into the role of CXCR3-dependent interactions in the development of primary, secondary and contraction of adaptive immune responses will therefore yield interesting results with applications for vaccinology.…”
Section: Cxcr3 In the Induction And Recall Of Immune Responsesmentioning
confidence: 99%
“…In contrast, CD4+ T EM cells gain access to reactive LNs via CXCR3-independent means to interact with DCs and increase future T cell priming through CD40 upregulation [49]. Once T EM cells enter the LN, it is unknown if CD8+ or CD4+ interactions with DCs are also dependent on CXCR3 and its ligands, although it has been shown that CD40L stimulated DCs increase expression of CXCL10 [77]. Future studies into the role of CXCR3-dependent interactions in the development of primary, secondary and contraction of adaptive immune responses will therefore yield interesting results with applications for vaccinology.…”
Section: Cxcr3 In the Induction And Recall Of Immune Responsesmentioning
confidence: 99%
“…In previous studies, different maturation methods caused differences in the type and characteristics of mDCs generated; indeed, the maturation signal can determine the type of the immune response (Krause et al 2007;Savina and Amigorena 2007;Ten Brinke et al 2007;Xia et al 2008). Among all methods, TNF-␣ and bacterial lipopolysaccharide (LPS) at different concentrations are the most frequently used single agents for maturation of DCs in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…IP-10 is also induced through cell-surface receptor interaction with T-cells [105][106][107][108][109][110]. IP-10 shares the chemokine (C-X-C motif) receptor (CXCR)3 with MIG and IFN-inducible T-cell a chemoattractant (I-TAC), an important receptor involved in the regulation of innate and adaptive immune responses through chemotaxis, cell growth and angiostasis [108,[111][112][113].…”
Section: Ip-10mentioning
confidence: 99%